Орос хэлний үгийн гарал үүслийн толь бичигт тэмдэглэсэн монгол үгс: Mongolian Words Marked in the Russian Etymology Dictionary - D., Enkhtuul (Mongolian Journal of Foreign Languages and Cultures, 2023)
This article is about borrowed words from Mongolian into Russian lexical found in different sources: ancient and modern language dictionary, local dialects, dictionary of foreign words, Russian- Mongolian dictionary, ancient Mongolian dictionaries, translations from the Secret History of Mongolia, Russian National Corpus [https://ruscorpora.ru] There are 18,000 words and phrases in the Russian Dictionary of Origins, from which 125 words or about 0.6 percent are marked as Mongolian, indicating the historical relationship between the Russian and Mongolian people, as well as the interaction between the two languages. Words borrowed from Mongolian to Russian are transformed adapting to the phonetic, grammatical, punctuation, and semantic norms of the target language. Many of these words in the Russian language are recognizable in form and remain old structure. Mongolian words borrowed into Russian are still actively used modern Mongolian referring to the Mongolian dictionary by Ya. Tsevel. The use of Mongolian words in Russian is declining, and it is possible to say with certainty the time of use.